2019
DOI: 10.1152/ajpgi.00046.2019
|View full text |Cite
|
Sign up to set email alerts
|

The developmentally regulated fetal enterocyte gene, ZP4, mediates anti-inflammation by the symbiotic bacterial surface factor polysaccharide A on Bacteroides fragilis

Abstract: Initial colonizing bacteria play a critical role in completing the development of the immune system in the gastrointestinal tract of infants. Yet, the interaction of colonizing bacterial organisms with the developing human intestine favors inflammation over immune homeostasis. This characteristic of bacterial-intestinal interaction partially contributes to the pathogenesis of necrotizing enterocolitis (NEC), a devastating premature infant intestinal inflammatory disease. However, paradoxically some unique pion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Evidence of many beneficial functions of Bacteroides strains suggests their intervention capabilities in lipopolysaccharide-induced immune response and gut microbiome shift, even having potential as therapeutic probiotics to prevent inflammatory disorders [ 18 , 19 ]. The polysaccharide A surface component of Bacteroides fragilis is mainly responsible for this protective effect [ 20 ]. The expression of polysaccharide A can also protect against central nervous system demyelination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of many beneficial functions of Bacteroides strains suggests their intervention capabilities in lipopolysaccharide-induced immune response and gut microbiome shift, even having potential as therapeutic probiotics to prevent inflammatory disorders [ 18 , 19 ]. The polysaccharide A surface component of Bacteroides fragilis is mainly responsible for this protective effect [ 20 ]. The expression of polysaccharide A can also protect against central nervous system demyelination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent studies have shown that the biological activities of B. fragilis-derived Polysaccharide A (PSA) and LPS are mediated by TLR4 activation. 60,62 Similarly, Ahmadi et al reported that B. fragilis and B. fragilis-derived outer membrane vesicles (OMVs, which contain bacterial components including LPS, outer membrane proteins, phospholipids, periplasmic components, DNA, RNA, hydrolytic enzymes and signaling molecules) both increase the mRNA levels of TLR4. 57 BFT, key virulence factor of ETBF, binds to an uncharacterized cell surface receptor, 63,64 triggering an array of signal transduction and contributing to key aspects of ETBF carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 EPSs were shown to protect from innate immune mechanism via AMPs the probiotic LGG after adhesion to IECs 46 (3b). PSA on B. fragilis or isolated PSA has been shown to inhibit IL-1β induced inflammation through interaction with TLR2 and 4 on IECs 47 , 48 (4a) and can also directly bind to antigen-presenting cells (dendritic cells) triggering downstream immune responses 49 , 50 (4b). Distinct adhesins in the bacteria cells, not belonging to any of the aforementioned class, could support the sustained effects of L. casei on IgA and calprotectin 51–54 (5).…”
Section: Adhesion Factors and Potential Downstream Mechanismsmentioning
confidence: 99%
“… 48 In addition, our novel study described the anti-inflammatory role of Zona pellucida protein 4 (ZP4). 47 ZP4 is a distinctive protein on immature fetal IECs that mediates PSA anti-inflammation effects by involving TLR2 and IL-8 47 ( Figure 1 ). IL-1β is a pro-inflammatory cytokine released mainly from intestinal macrophages during cell activation and acute inflammation.…”
Section: Adhesion Factors and Potential Downstream Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation